Digital Innovation for Child Protection Services in Subang Regency through an Integrated Information System - Layang Puspa Hanifah; Dealya Sulistia; Nur Azizah; Rian Piarna (Expert Net: Exploration Journal of Technological Education Trends, 2025)
The advancement of digital technology has become increasingly crucial in reforming public service delivery, particularly within child protection agencies. This research examines the implementation of an Integrated Child Protection Information System (SITPA) developed for Subang Regency's Regional Child Protection Commission (KPAD). SITPA consolidates multiple operational functions, including case intake, verification workflows, case tracking, and automated reporting, within a unified web platform. Development follows the Agile Scrum framework, enabling iterative refinement and continuous alignment with end-user requirements. Research data derives from field observations, stakeholder interviews, and examination of KPAD's existing paper-based procedures. Findings demonstrate that SITPA significantly improves data reliability, lightens administrative workload, and facilitates faster information flow across organizational units. The system further provides executive dashboards and structured analytics that support evidence-based decision-making. Implementation of this digital solution aims to strengthen the effectiveness, openness, and responsibility of child protection services throughout Subang Regency.